Research on Optimal Operation of Electricity Heat Hydrogen System Based on Evaluation of New Energy Consumption Potential - Liu, Xinrui; Zhao, Xinying; Zhong, Weiyang (Frontiers in Energy Research, 2021)
Under the background of "double high" power system, the electricity heat hydrogen hybrid system (EHHS) plays a significant role in the process of energy decarbonization. In order to meet the different optimization objectives of the system under different new energy consumption states, a new energy absorption potential assessment and operation optimization method of the EHHS based on intuitionistic fuzzy rough set theory is proposed. By using the intuitionistic fuzzy rough set theory, the continuous attribute data are divided into different grades and the results of membership and non-membership in different grades are obtained. The membership results of real-time absorption data are matched with the rule set, and then the determination results of absorption situation of the system are obtained. In this paper, the system absorption situation is divided into five parts. Compared with the traditional division, the system state can be described more comprehensively. At the same time, the fuzzy set is used to deal with the ambiguity of the boundary between each situation, and the intuition theory is used to solve the problem of the uncertainty of the absorption situation, so as to realize the accurate determination of the system absorption situation. Aiming at the specific consumption situation, an optimal scheduling model of equipment input for a specific EHHS is established, and a hybrid particle swarm optimization algorithm is used to solve the model. The results of the case analysis show that the dynamic state division method based on intuitionistic fuzzy rough set theory can better judge the system state according to the factors that change in real time, and the system optimization based on the absorption state division has the advantages of improving the operation economy and increasing the consumption of wind power.